Pengaruh Joyfull Learning terhadap Motivasi Belajar di SDN Karah I Surabaya - ALBERTA NOVARA PRINOTAMA; DIYAS AGE LARASATI; ANNA ROOSYANTI (Trapsila: Jurnal Pendidikan Dasar, 2019)
The purpose of this study was to determine the effect of Joyfull Learning methods on student motivation in social studies subjects at SDN Karah I Surabaya. This type of research used quasi-experimental (Quasi Experiment), the research approach is quantitative. The population research was 5th Grade Student of SDN Karah I Surabaya in academic year 2018/2019. The sample in this study were students of class V-A and V-B, amounting to 40 students in each class, researchers used this sample because from previous observations class V-A and V-B were still lacking motivation in learning. Based on the results of the analysis show that there is an influence of the level of motivation of students learning in class V by using the Joyfull Learning method, it can be seen that the significance value is 0,000 <0.05, so there is an influence of Joy Learning learning on learning motivation in social studies material class V SDN Karah I Surabaya.